Imaging Techniques and their Role in Dosage form Design and Drug Delivery Research - Franke, Susanne; Malcolmson, Carole; Bunt, Craig R.; Rupenthal, Ilva; Alany, Raid G. (Current Pharmaceutical Analysis, 2008)
The development and registration of pharmaceuticals often requires some degree of certainty around their in vivo performance. Many commonly used diagnostic and therapeutic imaging techniques have been attracting increasing interest to monitor the performance of dosage forms and drug delivery systems in vivo. The use of imaging and microscopy methods in dosage form design and drug delivery research is still in its infancy with only gamma scintigraphy being widely accepted by drug regulatory bodies as the method of choice for monitoring the gastrointestinal transit of oral dosage forms. The emerging use of ultrasonography and magnetic resonance imaging may potentially bring these techniques further to the scene with a more established role in the assessment of pharmaceutical dosage forms. This review compares and contrasts the scientific operation principles as well as advantages and disadvantages of some of these imaging techniques, including gamma scintigraphy, single photon emission computed tomography, positron emission tomography, radiology/computed tomography, ultrasonography magnetic resonance imaging and microscopy. Scientific articles are reviewed to give a broad overview of these techniques, their current applications and their future potential use in dosage form design and drug delivery research.
Keywords: Microscopy